Primary Leiomyosarcoma of Bone: A Rare Case Series with Review of Literature - Jitin Goyal; Bineeta Parihar; Nitin Agarwal; Sulagna Manna; Anila Sharma; Sunil Kumar Puri (Indian Journal of Medical and Paediatric Oncology)
Leiomyosarcoma (LMS) is an uncommon malignant spindle cell neoplasm of smooth muscles, accounting approximately 7% of soft tissue sarcoma. Primary LMS involving bone is an exceptional entity with very few cases described in the literature. The clinical, imaging, and pathological findings were analyzed retrospectively in three confirmed cases of primary LMS of bone. Pain and swelling were the patients' clinical symptoms. On imaging, LMS was often described as a solitary ill-defined lytic lesion with cortical breach depicted on radiograph or computed tomography (CT) scan. Magnetic resonance imaging (MRI) reveals a heterogeneous intermediate-hyperintense signal lesion on T2-weighted imaging (T2WI) with postcontrast enhancement. Histopathology reveals spindle cells arranged in fascicles with nuclear atypia and smooth muscle actin (SMA) positivity on immunohistochemistry (IHC)—consistent with diagnosis of LMS. The patients underwent surgical gross total resection with curative intent, followed by adjuvant chemotherapy or radiotherapy depending upon the stage and histological grade of LMS. On follow-up, the patients were disease free with no evidence of recurrence.